Fibrinogen-to-Albumin Ratio Links Systemic Inflammation to Osteoporotic Fractures and Shows Discriminative Performance Together with PLR, NLR, and MLR: Fibrinogen–Albumin Ratio and Inflammatory Markers in Osteoporotic Fractures - Fu, Youxin; Cao, Daigui; Liu, Zeyu; Liu, Zhiwei; Guo, Jianping; Zhou, Xu; Hao, Jie (Journal of Medical Biochemistry, 2026)
Background: Osteoporotic fracture (OPF) remains a major cause of disability in older adults. Laboratory-available composite indices integrating coagulation, inflammation, and nutritional status may facilitate risk stratification in patients with osteoporosis. Objective: To investigate the relationship between the fibrinogen-to-albumin ratio (FAR) and systemic inflammatory indices (platelet-to-lymphocyte ratio [PLR], neutrophil-to-lymphocyte ratio [NLR], and monocyte-to-lymphocyte ratio [MLR]) in osteoporosis, and to evaluate their discriminative value for identifying concurrent osteoporotic fractures. Methods: This retrospective study included 98 patients with osteoporosis admitted between January 2024 and May 2025, categorized into a fracture group (n=39) and a non-fracture group (n=59). FAR, PLR, NLR, and MLR were calculated from routine laboratory tests obtained within 24 h of admission. Group differences were assessed, Pearson correlation was used to examine associations between FAR and inflammatory indices, and logistic regression was performed to identify independent clinical/imaging correlates of fracture. Receiver operating characteristic (ROC) curves were constructed to evaluate discriminative performance. Results: FAR, PLR, NLR, and MLR were significantly higher in patients with osteoporosis complicated by fracture than in those without fracture (all P<0.001). FAR showed positive correlations with PLR, NLR, and MLR (all P<0.001). In multivariable analysis, age ≥60 years, lumbar–dorsal fascial injury, and the vertebral vacuum cleft sign were independently associated with fracture occurrence (all P<0.05). ROC analysis demonstrated high discriminative performance for FAR, PLR, NLR, and MLR, with AUCs of 0.900, 1.000, 0.998, and 0.983, respectively. Conclusions: FAR and leukocyte/platelet-derived inflammatory ratios were elevated in osteoporotic patients with fractures and were positively interrelated, supporting an inflammation–nutrition–coagulation laboratory phenotype in OPF. These routine laboratory indices showed strong discriminative performance for identifying concurrent osteoporotic fractures and may aid laboratory-based risk stratification in clinical practice.